2021
DOI: 10.1021/acs.oprd.1c00113
|View full text |Cite
|
Sign up to set email alerts
|

Solid Form Selection and Process Development of KO-947 Drug Substances

Abstract: KO-947 is a potent, selective extracellular signal-regulated kinases (ERK) inhibitor that was investigated in the clinic for the treatment of various solid tumors. KO-947 free base, form E, was originally recommended out of 10 identified crystalline forms for the development of an oral solid dosage product. Change of clinical need shifted the focus to aqueous solubility enhancement through salt formation. Mesylate salt demonstrated remarkably increased aqueous solubility and also profound polymorphism. Anhydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Second, three MEK inhibitors: trametinib, cobimetinib, and binimetinib have been approved in combination with B-RAF inhibitors. Third, the inhibitors of the final downstream kinase, ERK, are currently in clinical development, including LY3214496 (NCT02857270) [35], BVD-523 (NCT03417739) [36], MK-8353 (NCT01358331) [37], and KO-947 (NCT03051035) (Figure 5) [1,38].…”
Section: Inhibitors Of Ras Effector Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, three MEK inhibitors: trametinib, cobimetinib, and binimetinib have been approved in combination with B-RAF inhibitors. Third, the inhibitors of the final downstream kinase, ERK, are currently in clinical development, including LY3214496 (NCT02857270) [35], BVD-523 (NCT03417739) [36], MK-8353 (NCT01358331) [37], and KO-947 (NCT03051035) (Figure 5) [1,38].…”
Section: Inhibitors Of Ras Effector Proteinsmentioning
confidence: 99%
“…Third, the inhibitors of the final downstream kinase, ERK, are currently in clinical development, including LY3214496 (NCT02857270), [35] BVD-523 (NCT03417739), [36] MK-8353 (NCT01358331), [37] and KO-947 (NCT03051035) (Figure 5). [1] , [38]…”
Section: Inhibitors Of Ras Effector Proteinsmentioning
confidence: 99%
“…Our previous work successfully demonstrated that twin screw extrusion (TSE) could be used to scale up polymorphs of active pharmaceutical ingredients (APIs) . Polymorphism occurs when two or more crystals have the same chemical composition but different internal structures (molecular packing), while polymorph screening and the formation of crystalline salts/cocrystals are approaches used for optimization of physical properties such as melting point, hygroscopicity, chemical stability, and dissolution rate. Because of this, it is vital to develop robust crystallization processes for the isolation of the thermodynamically most stable form at room temperature. Therefore, one of the goals of this work was to see if TSE could again be utilized to apply mechanochemistry to generate gram-scale quantities of polymorphs of 1 to support phase mapping and crystallization to ensure form control. TSE has also become a popular way for generating pharmaceutical cocrystals and salts; thus, another goal was to determine if the hemihydrate of 2 could be isolated via liquid-assisted extrusion in an aqueous free environment via green chemistry.…”
Section: Introductionmentioning
confidence: 99%